The Relations between Politeness Strategies and Speech Acts: A Study Case of Bahasa Indonesia Learners from China at University - Hermalinda Pratiwi; Wahya; Kasno Pamungkas (Universitas Islam Negeri Palopo, 2026)
This study aims to examine the relations between politeness strategies and speech acts in Indonesian utterances spoken by Chinese students at Padjadjaran University. This study employs a qualitative descriptive method. The research participants were 16 Chinese exchange students from the Department of Indonesian Language at Guangxi Minzu University who were studying in the Department of Indonesian Literature at Padjadjaran University. Data were collected through observation and recording of conversations during class sessions. The data were analyzed using Searle’s speech act theory and Brown and Levinson’s politeness theory within a pragmatic approach. The results indicate that Chinese students employed three types of politeness strategies: positive politeness, negative politeness, and off-record strategies. The speech acts identified in the data included assertive, directive, and expressive speech acts. The analysis revealed that the type of speech act used by the speaker influences the choice of politeness strategy, as each speech act carries a different level of face threat. The novelty of this study lies in its demonstration that politeness strategies and speech acts are not separate pragmatic phenomena but are interrelated in interactive activities, including in BIPA classroom interactions. The findings of this study contribute to BIPA instruction and intercultural communication by highlighting the importance of pragmatic competence for foreign learners. This competence helps learners use Indonesian appropriately, politely, and in accordance with Indonesian sociocultural norms, thereby reducing the potential for misunderstandings in cross-cultural interactions.